SISTEM INFORMASI PEMASARAN DIGITAL BERBASIS WEB DENGAN MENGGUNAKAN METODE AGILE DI PT SAAMPARAN DIGITAL GROUP - Alvito Sabil Natarahayu; Tuti Rohayati; Dadan Mulyana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
PT Saamparan Digital Group is a company engaged in buying and selling YouTube accounts. Its marketing strategy still relies on traditional word-of-mouth methods, limiting promotional reach, slowing transactions, and increasing fraud risks. This study aims to design and develop a web-based digital marketing information system to expand market reach, enhance transaction security, and provide easy access to customer information.The research adopts the Agile Software Development method, which is iterative and flexible, allowing the system to be developed in stages according to user needs. The system was built using PHP, MySQL, and Bootstrap, with main features including product management, online transactions, reporting, and chat between users and administrators. System testing employed the black-box method to ensure functionality meets user requirements.The results show that the system improves PT Saamparan Digital Group’s marketing effectiveness by reaching wider markets, speeding up transaction processes, and reducing fraud risks through digital verification. Moreover, it provides a more convenient and secure shopping experience. Implementing this web-based digital marketing system is expected to strengthen the company’s competitiveness in the digital business era.